Efficient management of wireless IoT hydroponic systems using multi-node and hybrid Wi-Lo communication - Ja'afar, Abd Shukur; Rammes, Kahvisha; Othman, Mohd Azlishah; Misran, Mohamad Harris; Abdul Manap, Redzuan; Ali, Nur Alisa (Human Resource Management Academic Research Society, 2024)
Hydroponic gardening requires less room than soil-based cultivation and it provides precise control over environmental factors. The specific challenges of hydroponic systems with IoT can include the management of systems that receive and transmit large amounts of data especially in limited Wi-Fi coverage zone or Wi-Fi dead zone and analysing data wirelessly to assess the system's performance. This project aims to design and investigate an IoT-based hydroponic system that makes use of several multi-hop nodes for effective administration and communication. In this project involve with multi-node communication and each node connected to many sensor nodes. Each nodes will collect data from sensor and send to WiLo transceiver where the data will transfer wirelessly via Wi-Fi direct and Lora technology. The combination of these two techniques will form new network topology. The goal is to wirelessly connect all the nodes and establish communication in an appropriate topology in the hydroponic system. The multi-nodes communication system enables effective decisionmaking and problem-solving by facilitating real-time data sharing and cooperation. An investigation will be done at Line-of-sight and Non-Line of-Sight conditions. Based on the investigation, it is recommended that to avoid data loss, Wi-Fi direct node-to-node transmission should occur within a maximum range of 50 meters for 100% data reliability, while LoRa transmission can effectively cover within range of 150 meters.